Effective Communication : 25 Action-Based Articles Showing you what and How to Communicate for Maximum Effectiveness - Kehoe, Daniel (North Ryde McGraw-Hill, 2007)
It is a self-help book for employees and managers on how to communicate effectively.
Include Illustrations
Keywords: Business communication